Effects of carbon dioxide pneumoperitoneum on postoperative adhesion formation and oxidative stress in a rat cecal abrasion model. (September 2015) - Dalgic, Tahsin; Oymaci, Erkan; Bostanci, Erdal Birol; Cakir, Tebessum; Kece, Can; Erguder, Imge; Akoglu, Musa
Abstract: Introduction: It is claimed that CO2 pneumoperitoneum (CP) is less adhesiogenic than laparotomy. Our aim in this study was to investigate the local oxidative stress responses and related adhesion formation resulting from exposure to CP. Methods: Forty-five rats were randomised into six groups. Group 1 underwent laparotomy only; in group 2, 6 mmHg CP was performed for 60 min; in group 3, the same procedure was carried out using 12 mmHg CP; in group 4, laparotomy and cecal-peritoneal abrasion were performed; in group 5, 6 mmHg CP was performed for 60 min, followed by laparotomy and cecal-peritoneal abrasion; in group 6, the same procedure was carried out using 12 mmHg CP. Groups 1, 2 and 3 were sacrificed immediately and used only for biochemical examination. The other groups were sacrificed on the 14th postoperative day. Results: The total adhesion scores, thickness, quantity, extent and type of adhesions decreased steadily in groups 4, 5 and 6 (p < 0.05). The median values for neutrophil and monocyte infiltration, and for capillary and fibroblast proliferation decreased steadily in groups 4, 5 and 6 (p < 0.05). CAT, SOD and GSHPx levels decreased significantly in line with increasing pressure in groups 1, 2 and 3. SOD and GSHPx levels were similar in groups 4, 5 and 6, while CAT levels decreased with increasing pressure in groups 4, 5 and 6. Conclusion: It was found that CP is associated with less adhesion formation than laparotomy in the presence of similar antioxidant levels. The reduced adhesion formation is probably caused by a decreased inflammatory response. Highlights: Increased CO2 pneumoperitoneum pressure ended with better adhesion parameters. Increased CO2 pneumoperitoneum pressure caused decreased oxidative stress markers. Neutrophil infiltration and capillary, fibroblast proliferation decreased steadily with increased pressures.